Magnetite Particle Presence in the Human Brain: A Computational Dosimetric Study to Emphasize the Need of a Complete Assessment of the Electromagnetic Power Deposition at 3.5 GHz - Vatamanu, D.; Miclaus, S. (Engineering, Technology & Applied Science Research, 2021)
The growing evidence of increased magnetite nanoparticles (both endo- and exo-genic) in the human brain raises the importance of assessing the entire power deposition when electromagnetic waves at GHz frequencies propagate in such tissues. This frequency range corresponds to many popular portable communication devices that emit radiation close to a human’s head. At these frequencies, the current dosimetric numerical codes can not accurately compute the magnetic losses part. This is due to the lack of an implemented computational algorithm based on solving the coupled Maxwell and Landau-Lifshitz-Gilbert equations, in the case of magneto-dielectrics, considering eddy currents losses and specific properties of magnetic sub-millimetric particles. This paper focuses on analyzing the limits and the inconsistencies when using commercial dosimetric numerical software to analyze the total absorbed power in brain models having ferrimagnetic content and being exposed to 3.5GHz electromagnetic waves. Magnetic losses computed using Polder’s permeability tensor as constitutive relation lead to unreliable results. However, using such software can provide a preliminary view of the electromagnetic impact of ultra- and super-high frequencies on magnetic-dielectric tissues.